Checklist of flora along tourist trails to Mt. Lamongan, East Java (Indonesia): misconception of restoration and ecotourism programs in mountain region? - Luchman Hakim; Brian Rahardi; Arief Rachmansyah (Brawijaya University, 2018)
The aim of this research was to evaluate the diversity of plant species along the tourist trails to Mt. Lamongan and combat any misconceptions about ecosystem restoration and the ecotourism development program in Mt. Lamongan. A floristic survey was done through flora identification along the hiking trail from the gate of Mt. Lamongan nature recreation area in Papringan Village to the slopes of Mt. Lamongan. The identified species were listed and their taxonomic status analyzed using information from the GRIN website. This study found that exotic plant species are abundant along the tourist tract. Human activities were identified as contributing to the introduction and establishment of exotic plant species. Result of the research indicate that restoration knowledge and techniques do not exist in the Mt. Lamongan region. A comprehensive evaluation of flora should be implemented to enhance the restoration program and protect forest area, especially the tourist corridor to the peak of Mt. Lamongan. Integrated actions to enhance restoration and promote tourism are needed. It encompasses strengthening the restoration concept and technology, eradication of exotic plant species, and establishing a proper tourism interpretive tract.